2014
DOI: 10.1016/j.neuroimage.2013.05.070
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c oxidase response to changes in cerebral oxygen delivery in the adult brain shows higher brain-specificity than haemoglobin

Abstract: The redox state of cerebral mitochondrial cytochrome c oxidase monitored with near-infrared spectroscopy (Δ[oxCCO]) is a signal with strong potential as a non-invasive, bedside biomarker of cerebral metabolic status. We hypothesised that the higher mitochondrial density of brain compared to skin and skull would lead to evidence of brain-specificity of the Δ[oxCCO] signal when measured with a multi-distance near-infrared spectroscopy (NIRS) system. Measurements of Δ[oxCCO] as well as of concentration changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
94
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 52 publications
4
94
3
1
Order By: Relevance
“…It has been claimed that chromophore cross-talk, insufficient separability due to physical noise, and any concurrent changes in scattering can all give rise to spurious ∆[oxCCO] traces [12,22]. Yet, recent studies disprove these claims and establish ∆[oxCCO] as a NIRS-derived indicator of the redox state of mitochondrial cytochrome c oxidase and hence as a brain-specific optical biomarker of cerebral metabolic status [5,[8][9][10][11]14,15,32,33]. Also note that our study employs a restrictive wavelength range of 780-900 nm; exclusion of shorter wavelengths helps to enhance the contribution of cytochrome c oxidase to attenuation signals [14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been claimed that chromophore cross-talk, insufficient separability due to physical noise, and any concurrent changes in scattering can all give rise to spurious ∆[oxCCO] traces [12,22]. Yet, recent studies disprove these claims and establish ∆[oxCCO] as a NIRS-derived indicator of the redox state of mitochondrial cytochrome c oxidase and hence as a brain-specific optical biomarker of cerebral metabolic status [5,[8][9][10][11]14,15,32,33]. Also note that our study employs a restrictive wavelength range of 780-900 nm; exclusion of shorter wavelengths helps to enhance the contribution of cytochrome c oxidase to attenuation signals [14].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous experimental and clinical studies have been carried out to delineate the biological basis of optical signals obtained from healthy and injured brain. These studies present sound evidence that NIRS-derived changes in chromophore concentrations can act as markers of cerebral physiology and pathology; the results offer significant insights into the feasibility of NIRS for observation of functional activation [5,6], detection of autoregulation or metabolic failure during routine surgery or after brain injury [7,8], and assessment of impending neurological damage due to hypoxia-ischemia (HI) in adults or neonates [9][10][11].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The total concentration of CCO in the short term is almost constant and it interconverts between reduced and oxidized states. The concentration changes of oxidized CCO (Δ[ox-CCO]) that can be monitored by NIRS represent changes in the CCO redox state and reflect the balance between cerebral oxygen delivery and utilization [4,5]. The brain cells have the highest mitochondrial density among all other body cells thus the concentration of CCO is significantly higher and easier to measure within brain tissue.…”
Section: Introductionmentioning
confidence: 99%
“…[8] In a study that was published in 2013 which points the influence of the variations in blood flow and pressure on systemic and cerebral oxygen saturation during CPB found that the maintenance of flow and thus DO2 was more important than the maintenance of mean arterial pressure (MAP). [9] In the same study, a phenylephrine-induced increase in MAP led to the decrease of cerebral oxygen saturation (Sco2) and thus to the DO2 to the brain.…”
Section: Blood Flow During Cpb: Goals and Requirementsmentioning
confidence: 99%